Answer:
(c) 2
Step-by-step explanation:
2(x - 4) + 7 = 3
2x + 2(-4) + 7 = 3
2x - 8 + 7 = 3
2x - 1 = 3
2x - 1 + 1 = 3 + 1
2x = 4
2x/2 = 4/2
x = 2
Hope this helps!!!
Answer:
100 lol
Step-by-step explanation:
ty for the points! <3
(6x–1)(6x+1) - 4x(9x+2) = −1
Simplify the left side:
36x^2-1 -36x^2-8x = -1
Combine like terms:
-1 -8x = -1
Add 1 to both sides:
-8x = 0
Divide both sides by -8:
x = 0 / -8
x = 0
The root is 0
Step-by-step explanation:
Jupiter's
Jupiter's menagerie of moons includes the largest in the solar system (Ganymede), an ocean moon (Europa) and a volcanic moon (Io). Many of Jupiter's outer moons have highly elliptical orbits and orbit backwards (opposite to the spin of the planet).
i want 3 brainliest